The relationship between anthropometric characteristics and physical fitness parameters of figure skating athletes - Kutlay, E.; Haslofça, F.; Haslofça, E. (European Journal of Physical Education and Sport Science, 2020)
In order to monitor training effects and physical developments in elite sports, it may be beneficial to perform anthropometric measurements and physical fitness tests regularly. In this study, the relationship between the anthropometric properties and physical fitness values of elite figure skating athletes were investigated. 21 elite athletes in the 11-16 age group, female (n=12) and male (n=9), participated in the study. Anthropometric measurements were taken in accordance with The International Society for the Advancement of Kinanthropometry (ISAK) protocol. S6 and S8 skinfold thickness, body fat ratio (BF%), body mass index (BMI), Manouvrier Index (MI), waist/hip ratio and somatotype components in girls Group II, III and in boys Group II were calculated. Also, balance, flexibility, handgrip strength, vertical jump, agility, medicine ball overhead back throw, speed, and endurance tests were applied to all groups. Descriptive statistical analyzes were made using the IBM SPSS 25.0 statistics program. The relationship between variables was calculated by the Pearson Correlation coefficient. The significance level was taken as p<0.01 and p<0.05. In boys, body weight, body height and arm span, sitting height, BMI, humerus breadth and foot length were observed to be associated with all physical fitness parameters (p<0.01, p<0.05), except balance and agility; Girth measurements were related to handgrip strength, vertical jump, overhead medicine ball backward throw, speed and endurance (p<0.01, p<0.05). Negative relationships of the endomorphic feature with flexibility and endurance were determined (p<0.05). In girls, it was found that body weight, body height, and arm span, sitting height and BMI were related to flexibility, handgrip strength, medicine ball overhead back throw (p<0.01, p<0.05); girth measurements were found to be related to flexibility, handgrip strength, vertical jump, overhead medicine ball back throw (p<0.01, p<0.05); also, significant correlations (p<0.01, p<0.05) were found between the handgrip strength and breadth measurements. Assessment of the relationship between morphological features and motor skills with specific field tests and standardized tests performed at regular intervals in athletes can contribute to the athletes' selection and training planning of the relevant federations and orientating towards their goals.